FRI0424 Role of baseline c-reactive protein in response to infliximab plus naproxen vs naproxen alone in patients with axial spondyloarthritis in the infast study. (23rd January 2014) - Sieper, J.; Rudwaleit, M.; Lenaerts, J.; Wollenhaupt, J.; Myasoutova, L.; Park, S.; Song, Y.; Yao, R.; Govoni, M.; Chitkara, D.; Vastesaeger, N.
Abstract : Background: Baseline inflammation has been shown to influence response to TNF alpha antagonist treatment in patients with axial spondyloarthritis (SpA). Objectives: To evaluate the role of C-reactive protein (CRP) in the response to treatment with infliximab (IFX)+nonsteroidal anti-inflammatory drugs (NSAIDs) vs NSAIDs alone in patients with axial SpA who have early, active disease. Methods: The INFAST trial was a double-blind, randomized controlled trial of IFX in biologic-naïve patients 18–48 years of age with early, active axial SpA (ASAS criteria, disease duration ≤3 years, chronic back pain, and active inflammation of the SI joints on MRI). Patients naïve to NSAIDs or treated with a submaximal dose of NSAIDs were randomized (2:1) to receive 28 weeks of treatment with either IV IFX 5 mg/kg (weeks 0, 2, 6, 12, 18, and 24)+naproxen (NPX) 1000 mg/d or IV placebo (PBO)+NPX 1000 mg/d. ASAS partial remission was evaluated in patients with high CRP (>upper limit of normal [ULN], per local laboratory limits) or low CRP (≤ULN). Response was also evaluated in patients who met the NY modified criteria for AS by SI X-ray (bilateral ≥grade 2 or unilateral ≥grade 3, based on local rheumatologist judgement) and were not naïve to NSAIDs (AS group) versus patients who did not meet radiographic criteria for AS (nr-axSpA group). Data were analyzed descriptively. Results: 156 patients were included in efficacy analyses. Overall, ASAS partial remission rate was greater for the IFX+NPX group (n=105) than the PBO+NPX group (n=51) (61.9% vs 35.3%, P =0.0021). For patients treated with IFX+NPX, partial remission rate was greater in the 49 patients with high CRP than in the 44 with low CRP (71.4% vs 59.1%). However, for patients treated with NPX alone, remission rates were similar whether CRP was high or low (40.7% [n=27] vs 38.5% [n=13]). In analysis of the AS and nr-axSpA groups, partial remission was greater in the AS group than the nr-axSpA group after treatment with IFX+NPX (72.2% [n=54] vs 56.4% [n=39]); after treatment with NPX alone, partial remission was greater in the nr-axSpA than the AS group (46.7% [n=25] vs 36.0% [n=15]). This pattern might be explained by the higher baseline mean CRP values in the AS group (n=83) than the nr-axSpA group (n=63) (CRP 2.59 vs 0.92 mg/dL). Within the AS group, the difference between the 2 treatments was clear in patients with high baseline CRP (IFX+NPX, 75.8% [n=33] vs NPX, 30% [n=20]); but not with low baseline CRP (IFX+NPX, 66.7% [n=21] vs NPX, 60% [n=5]). This pattern was not observed in the nr-axSpA group, perhaps because of low baseline CRP or because of the small number of subjects available for analysis. Conclusions: Elevated baseline CRP was associated with a better response to IFX therapy, even within a population of axial SpA patients with early disease and established MRI inflammation at baseline. Disclosure of Interest: J. Sieper Grant/research support from: Abbott, Merck, Pfizer, Janssen, Consultant for: Abbott, Merck, Pfizer, UCB, Roche, Lilly, Novartis, Speakers bureau: Merck, Abbott, Pfizer, UCB, M. Rudwaleit Consultant for: Abbott, BMS, MSD, Pfizer, UCB, Speakers bureau: Abbott, BMS, MSD, Pfizer, UCB, Roche, J. Lenaerts Consultant for: Abbott, BMS, MSD, Pfizer, Roche, Astra Zeneca., J. Wollenhaupt Consultant for: Abbott, Biotest, BMS, Chugai, MSD, Medac, Merck, MSD, Pfizer, Roche, and UCB., Speakers bureau: Abbott, Biotest, BMS, Chugai, MSD, Medac, Merck, MSD, Pfizer, Roche, and UCB., L. Myasoutova: None Declared, S. Park: None Declared, Y. Song: None Declared, R. Yao Employee of: Merck, M. Govoni Employee of: Merck, D. Chitkara Employee of: Merck, N. Vastesaeger Employee of: Merck